Salihara Lodging as a Small and Medium Business - Soraya, Zahra; Agustiani, Fitri; Pradini, Gagih; Kusumaningrum, Anisa Putri (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Lodging is a business that has developed quite rapidly because competition between companies is getting tighter because of the increasing number of similar restaurants offered. This competition will have an impact on the company because the tighter the competition, consumers will have a selection of the product. MSMEs (Micro, Small and Medium Enterprises) play a very large role in advancing the Indonesian economy. Apart from being one of the new job alternatives, MSMEs also played a role in encouraging the pace of economic growth after the 1997 monetary crisis when large companies experienced difficulties in developing their businesses. Currently, MSMEs have contributed greatly to regional income and Indonesian state revenue. This journal discusses one of the inns in the Pasar Minggu area, in this study, we analyze a SWOT (Strengths, Weaknesses, Opportunities, Threats) of the inn